Exploring the influence of the spiritual climate on psychological empowerment among nurses in China: a cross-sectional study - Xuan Wang; Yulan Xia; Li Gou; Xianxiu Wen (BMC, 2024)
Abstract Background Psychological empowerment notably impacts nurses' work engagement and high-quality care. A spiritual climate is a work environment that respects individuals and encourages them to express personal views. Previous studies have shown that a spiritual climate enhances psychological empowerment, however, the relationship between them among the nursing population remains unclear. This study aimed to explore the effect of a spiritual climate on nurses' psychological empowerment and provide a scientific basis for improving psychological empowerment among nurses. Methods A cross-sectional survey of 837 nurses from five hospitals in Sichuan Province, Southwest China, was conducted using a convenience sampling method; this survey included nurses' demographic characteristics, the Psychological Empowerment Scale (PES), and the Chinese version of the Spiritual Climate Scale (C-SCS). The data were analysed using one-way analysis of variance (ANOVA), correlation analysis, and multiple linear regression. Results The sample of 837 nurses attained a psychological empowerment score of (45.49 ± 6.42) and a spiritual climate score of (75.25 ± 16.75). The one-way ANOVA revealed that psychological empowerment scores among nurses varied based on differences in age, department, years of work experience, professional title, level of work intensity, and children (yes/no). Pearson's correlation analyses revealed a significant positive correlation between the spiritual climate and nurses' psychological empowerment (r = 0.564, P < 0.001), and multiple linear regression analysis showed that working in the intensive care unit (ICU), work intensity, and the four items pertaining to spiritual climate influenced nurses' psychological empowerment, explaining 32.6% of the total variance in psychological empowerment. Conclusion The findings suggested that the spiritual climate perceived by nurses and psychological empowerment are moderately high. Working in the ICU, work intensity, and the four items pertaining to spiritual climate influence nurses' psychological empowerment. Nursing managers should pay attention to the daily work intensity of nurses, especially ICU nurses, organize work tasks reasonably, promote dynamic and balanced nurse human resource deployment based on patients' conditions and nurses' workloads, and implement scientific scheduling plans to establish a positive spiritual climate in the workplace. Additionally, group workshops and systematic training programs can effectively enhance psychological empowerment among nurses.